Cyclic GMP-dependent protein kinase-I localized in nociceptors modulates nociceptive cortical neuronal activity and pain hypersensitivity. Issue 1 (April 2017) - Gangadharan, Vijayan; Wang, Xu; Luo, Ceng
Chronic pain represents a frequent and poorly understood public health issue. Numerous studies have documented the key significance of plastic changes along the somatosensory pain pathways in chronic pain states. Our recent study demonstrated that the cGMP-dependent protein kinase I (PKG-I) specifically localized in nociceptors constitutes a key mediator of hyperexcitability of primary sensory neurons and spinal synaptic plasticity after inflammation. However, whether PKG-I in nociceptors further affects the cortical plasticity in the ascending pain pathways under pathological states has remained elusive. The immediate-early gene c-fos and phosphorylated ERK1/2 (pERK1/2) are considered reliable indicators for the neuronal activation status and it permits a comprehensive and large-scale observation of nociceptive neuronal activity along the ascending pain pathways subjected to tissue injury. In the present study, we systemically demonstrated that peripheral injury in PKG-I fl/fl mice produced a significant upregulation of c-Fos or pERK1/2 over from the periphery to the cortex along the pain pathways, including dorsal root ganglion, spinal dorsal horn, ventral posterolateral thalamus, primary somatosensory hindlimb cortex, anterior cingulate cortex, basolateral amygdala, periaqueductal gray, and parabrachial nucleus. In contrast, very few cells in the above regions showed c-Fos or pERK1/2 induction in nociceptor-specific knockout mice lacking PKG-I (SNS-PKG-I −/− mice). Our results indicate that PKG-I expressed in nociceptors is not only a key determinant of dorsal root ganglion hyperexcitability and spinal synaptic plasticity but also an important modulator of cortical neuronal activity in pathological pain states and represent what we believe to be novel targets in the periphery for pain therapeutics.